Characterization of binding of antipsychotics to muscarinic receptors using mouse cerebral cortex - Keisuke Obara; Saki Horiguchi; Toma Shimada; Takumi Ikarashi; Fumiko Yamaki; Kazuhiro Matsuo; Takashi Yoshio; Yoshio Tanaka (Elsevier, 2019)
Antipsychotics are often the first-line treatment for behavioral and psychological symptoms of dementia. However, the potential anticholinergic effects of antipsychotics could counteract the therapeutic effects of cholinesterase inhibitors used to treat dementia. We investigated the inhibitory effects of 26 antipsychotics on [N-Methyl-3H]scopolamine specific binding in mouse cerebral cortex. At 10−5 M, chlorpromazine, levomepromazine, prochlorperazine, timiperone, zotepine, pimozide, blonanserin, olanzapine, quetiapine, and clozapine inhibited [N-Methyl-3H]scopolamine binding by > 45%. Furthermore, the pKi values of chlorpromazine, levomepromazine, zotepine, olanzapine, and clozapine overlapped with their clinically achievable blood concentrations. Therefore, the anticholinergic properties of these antipsychotics could attenuate the effects of cholinesterase inhibitors. Keywords: Antipsychotics, Anticholinergic effect, Mouse cerebral cortex